2006
DOI: 10.1167/iovs.06-0362
|View full text |Cite
|
Sign up to set email alerts
|

Human Scleral Hydraulic Conductivity: Age-Related Changes, Topographical Variation, and Potential Scleral Outflow Facility

Abstract: Quantifying HC may help refine ocular pharmacotherapy, as transscleral water movement increases intraocular drug elimination and impedes transscleral drug delivery. The potential scleral outflow is two to three times higher than that which occurs in vivo; hence, medical or surgical interventions that fully exploit this pathway have considerable capacity to lower intraocular pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 28 publications
4
31
0
Order By: Relevance
“…39 In this study, we found that there was lower permeability to dextran in older CD1 than in younger CD1 mice. Related measures of scleral permeability, namely hydraulic conductivity and permeability to albumen, have been reported to decline with age in human eyes, 40,41 and these findings are consistent with our permeability data. We have recently found that older CD1 mice are more susceptible to experimental glaucoma damage than younger CD1 mice.…”
Section: Discussionsupporting
confidence: 92%
“…39 In this study, we found that there was lower permeability to dextran in older CD1 than in younger CD1 mice. Related measures of scleral permeability, namely hydraulic conductivity and permeability to albumen, have been reported to decline with age in human eyes, 40,41 and these findings are consistent with our permeability data. We have recently found that older CD1 mice are more susceptible to experimental glaucoma damage than younger CD1 mice.…”
Section: Discussionsupporting
confidence: 92%
“…25 However, there is evidence to suggest that for some ethnic groups a significant age-dependent decrease in CCT occurs in later life. [26][27][28] In comparison, Jackson et al 24 reported that although ST showed a possible reduction with age, the trend was not significant. In our study in whites, we found that age did not influence CCT or ST measurements.…”
Section: Discussionmentioning
confidence: 92%
“…Perhaps, corneal thickness (and curvature) might be uniquely affected by hormonal changes even though sex-related difference in CCT remains to be adequately defined. 23 Jackson et al 24 reported that there were no difference in the ST between males and females. However, the site where the ST was measured on donor eyes was randomly selected.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have demonstrated the integrity of tissue clamped in this Ussing chamber. 13,15,16,17 A small glass encased magnetic stirrer was added to each hemi-chamber. Previous studies have demonstrated that stirring does not increase the scleral permeability of high MWT compounds.…”
Section: Diffusion Testing Apparatusmentioning
confidence: 99%